2023
DOI: 10.1186/s13102-023-00631-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychological readiness is related to return to sport in judo injuries: a cross-sectional study

Abstract: Background The aim of this study is to investigate the influence of a judoka's psychological readiness in relation to his ability to return to sport. At the present time, the relationship between physical and psychological readiness to return to sport has not been adequately elucidated. Methods This is a cross-sectional study. An online survey was distributed via social networks and the German Judo Association collecting data from competitive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In terms of physical preparation for competition, we evaluated the efficacy of a specific judo injury prevention warm-up program supervised by a coach on the overall injury prevalence and concluded that the intervention did not significantly reduce the prevalence of overall and severe injuries [33]. We found that the type of injury, sport level, treatment method and gender seemed to influence the judoka's psychological preparation and ability to return to sports after injury [34]. However, in the present study no differences were observed between sexes in the external rotation of the athletes participating in the study, neither in the dominant nor in the non-dominant leg.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of physical preparation for competition, we evaluated the efficacy of a specific judo injury prevention warm-up program supervised by a coach on the overall injury prevalence and concluded that the intervention did not significantly reduce the prevalence of overall and severe injuries [33]. We found that the type of injury, sport level, treatment method and gender seemed to influence the judoka's psychological preparation and ability to return to sports after injury [34]. However, in the present study no differences were observed between sexes in the external rotation of the athletes participating in the study, neither in the dominant nor in the non-dominant leg.…”
Section: Discussionmentioning
confidence: 99%
“…Lambert et al [34] found that the type of injury, sport level, treatment method and gender seemed to influence the judokaʹs psychological preparation and ability to return to sport after injury. However, in the present study no differences were observed between sexes in the external rotation of the athletes participating in the study, neither in the dominant nor in the non-dominant leg.…”
Section: Discussionmentioning
confidence: 99%